2D Nanosheets and Their Composite Membranes for Water, Gas, and Ion Separation. Issue 49 (18th July 2019) - Kim, Seungju; Wang, Huanting; Lee, Young Moo
Abstract: Two‐dimensional nanosheets have shown great potential for separation applications because of their exceptional molecular transport properties. Nanosheet materials such as graphene oxides, metal–organic frameworks, and covalent organic frameworks display unique, precise, and fast molecular transport through nanopores and/or nanochannels. However, the dimensional instability of nanosheets in harsh environments diminishes the membrane performance and hinders their long‐term operation in various applications such as gas separation, water desalination, and ion separation. Recent progress in nanosheet membranes has included modification by crosslinking and functionalization that has improved the stability of the membranes, their separation functionality, and the scalability of membrane formation while the membranes' excellent molecular transport properties are retained. These improvements have enhanced the potential of nanosheet membranes in practical applications such as separation processes. Abstract : Modification of nanosheet membranes by crosslinking and functionalization has improved their stability, their separation functionality, and the scalability of membrane production while retaining the membranes' excellent molecular transport properties. These improvements have enhanced the potential of nanosheet membranes in practical applications such as separation processes.